2022
DOI: 10.1371/journal.pntd.0010489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratory parameters and fatality of Severe fever with thrombocytopenia syndrome patients: A systematic review and meta-analysis

Abstract: Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease with high case fatality rate. Unfortunately, no vaccine or antiviral specifically targeting SFTS virus (SFTSV) are available for the time being. Our objective was to investigate the association between clinical laboratory parameters and fatality of SFTS patients. Methods The systematic review was conducted in accordance with The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
6
21
1
Order By: Relevance
“…The overall case fatality rate was 6.1% in Jiangsu province from 2011 to 2022. The results were slightly lower than those reported in other studies ( 16 21 ). The majority of SFTS fatal cases reported in Jiangsu province mostly occurred in the western and southern hilly regions.…”
Section: Discussioncontrasting
confidence: 84%
“…The overall case fatality rate was 6.1% in Jiangsu province from 2011 to 2022. The results were slightly lower than those reported in other studies ( 16 21 ). The majority of SFTS fatal cases reported in Jiangsu province mostly occurred in the western and southern hilly regions.…”
Section: Discussioncontrasting
confidence: 84%
“…Concerning laboratory parameters, previous studies demonstrated that decreased levels of PLT, ALC, and MON% (monocyte percentage) were strongly associated with an increased risk of death in SFTS patients. However, WBC was not associated with SFTS outcomes, although leukopenia was a typical feature of SFTS ( 26 , 27 ). NLR (neutrophil-to-lymphocyte ratio) and PLR (platelet-to-lymphocyte ratio) are regarded as prognosis indicators in SFTS and an increased NLR is connected to a greater risk of death in SFTS patients ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SFTSV invasion activates host immune responses, breaks the balance of immunocytes, and releases abundant cytokines and chemokines. The cytokine storm contributes to multiple organ damage in SFTS patients 23 . The NLR is an inflammatory indicator that assesses the severity and prognoses of SFTS.…”
Section: Discussionmentioning
confidence: 99%